QUANTITATIVE 2-D FUEL VAPOR CONCENTRATION MEASUREMENTS IN AN EVAPORATING DIESEL SPRAY USING THE EXCIPLEX FLUORESCENCE METHOD - Kim, Tongwoo (My University, 2009)
To experimentally investigate evaporating sprays under conditions experienced in high speed direct-injection (HSDI) diesel engines, the exciplex (excited state complex) laser-induced fluorescence technique and high-speed natural luminosity cinematography were applied for non-reacting and reacting diesel sprays respectively, in a combustion-type constant-volume spray chamber. The combustion-type spray chamber was developed and provides conditions representative of a diesel engine at the start of fuel injection with good repeatability. A detailed set of calibration experiments were performed in order to quantify the TMPD (tetramethyl-p-phenylene-diamine) fluorescence signal. The effects of pressure and collision partner were found to be negligible. The effect of temperature was found to increase the fluorescent yield up to 600 K, then decrease it for further increases in temperature. An adiabatic mixing model for the estimation of the temperature reduction due to vaporization allowed correction of the temperature effects, and laser beam absorption and laser spatial non-uniformity were also corrected in the final calibration procedure. To assess the accuracy of the calibration procedure, the fuel vapor concentration was integrated and found to agree well with the mass of fuel injected (< 10%) after the end of injection when all the liquid fuel was vaporized. Estimation of the uncertainty of the measurements was 21%. Using a density of 15 kg/m3 the effects of three ambient gas temperatures (800, 1000 and 1200 K), three peak injection pressures (60, 90 and 150 MPa) and three nozzle hole sizes (0.14, 0.158 and 0.2 mm) were investigated based on the calibrated exciplex concentration measurements. Limited experiments were performed at 7.5 kg/m3. The data indicate that early in the injection event liquid and vapor coexist at the spray leading edge, however the liquid length reaches a terminal value and the vapor phase continues to penetrate. Lower ambient gas density were shown to provide faster vapor penetration and longer liquid lengths. Higher ambient gas temperatures were shown to produce a wider radial vapor extent with higher equivalence ratios and higher gradients at the edge of the jet. Distributions of the vapor concentration for higher injection pressures showed faster fuel vaporization rates and larger spray head volumes. Larger nozzle hole sizes were shown to have faster vapor-phase penetration rates and longer liquid lengths. The effects of the aforementioned parameters on the spray-spreading angle were shown to be transient in nature although as injection progressed the steady values were achieved. Natural luminosity images from reacting diesel sprays were acquired and compared with the exciplex image data to understand the equivalence ratio distribution during the ignition and initial flame development period. As a result, the first detection of the chemiluminescence signals seems to occur in fuel-rich vapor regions near the boundary of the liquid core with an equivalence ratio near 2 and a temperature of approximately 800 K. These conditions were found to be independent of injection pressure and nozzle diameter for the condition tested (15 kg/m3 and 1000 K ambient).